Levodopa/carbidopa intestinal gel infusion and weight loss in Parkinson's disease. (18th November 2018) - Fabbri, M.; Zibetti, M.; Beccaria, L.; Merola, A.; Romagnolo, A.; Montanaro, E.; Ferreira, J. J.; Palermo, S.; Lopiano, L.
Abstract : Background and purpose: Weight loss (WL) is a frequent yet under‐recognized complication of levodopa/carbidopa intestinal gel (LCIG) infusion, as well as a milestone of Parkinson's disease (PD) disability progression. The complex association between WL, poor nutritional status, motor complications and PD progression, however, remains unclear. Methods: Consecutive consenting patients with PD treated with LCIG ( n = 44; PD duration, 18.3 ± 6.5 years) were enrolled in an open‐label observational study assessing the extent of WL occurring during LCIG treatment. As secondary aims, we correlated the nutritional status, as detected by the Mini Nutritional Assessment, with the severity of motor symptoms [Movement Disorder Society Unified Parkinson's Disease Rating Scale part III], motor complications (Unified Parkinson's Disease Rating Scale part IV), activities of daily living (Schwab and England scale), cognitive impairment (Mini Mental State Examination), depression (Beck Depression Inventory), difficulties in feeding (Edinburgh Feeding Evaluation in Dementia Questionnaire) and levodopa equivalent daily dose (LEDD). Results: There was an average WL of 9.9 ± 10.5% (7.6 ± 7.1 kg) over an LCIG treatment period of 51.6 ± 28.5 months. The extent of WL correlated with the percentage of the waking day spent with dyskinesia ( P < 0.05). The nutritional status correlated with motor symptom severity ( P < 0.01), dysphagia ( P < 0.01) and LEDD ( P < 0.01). Conclusions: Weight loss may occur in patients with PD undergoing LCIG in correlation with the percentage of the waking day spent with dyskinesia. Regardless of the extent of WL, the nutritional status correlated with higher LEDD, as well as with indices of disease progression, such as motor symptom severity and dysphagia.